Synergies in Hospitality: Exploring Strategic Partnership and Collaboration for Business Success - Ayush Kumar Ojha (Journal of Social Responsibility, Tourism and Hospitality, 2021)
This research paper delves into the strategic dynamics of partnership and collaboration within the hospitality industry. Focused on enhancing business success, the study explores how synergies between stakeholders contribute to improved operational efficiency, guest experiences, and sustainable growth. By examining key areas such as supplier relationships, technology integration, marketing initiatives, and community engagement, the paper aims to provide valuable insights into the nuanced landscape of partnerships in hospitality. Through a concise yet comprehensive analysis, the research offers practical considerations and actionable recommendations for businesses aiming to leverage collaborative strategies for heightened competitiveness and customer satisfaction in the dynamic hospitality sector.